SARS-CoV-2 surveillance by RT-qPCR-based pool testing of saliva swabs (lollipop method) at primary and special schools-A pilot study on feasibility and acceptability. - Anika Kästner; Petra Lücker; Martina Sombetzki; Manja Ehmke; Nicole Koslowski; Swantje Mittmann; Arne Hannich; Antje Schwarz; Kristian Meinck; Lena Schmeyers; Katrin Schmidt; Emil C Reisinger; et al. (PLoS ONE, 2022)
Background Since the onset of the COVID-19 pandemic, children have been mentally and physically burdened, particularly due to school closures, with an associated loss of learning. Therefore, efficient testing strategies with high sensitivity are necessary to keep schools open. Apart from individual rapid antigen testing, various methods have been investigated, such as PCR-based pool-testing of nasopharyngeal swabs, gargle, or saliva samples. To date, previous validation studies have found the PCR-based saliva swab pool testing method to be an effective screening method, however, the acceptability and feasibility of a widespread implementation in the school-setting among stakeholders has not been comprehensively evaluated. Methods In this pilot study, SARS-CoV-2 saliva swab pool testing of up to 15 swabs per pool was conducted in ten primary and special schools in Mecklenburg-Western Pomerania, Germany, over a period of one month. Thereafter, parents, teachers and school principals of the participating schools as well as the participating laboratories were surveyed about the feasibility and acceptability of this method, its large-scale implementation and challenges. Data were analyzed quantitatively and qualitatively. Results During the study period, 1,630 saliva swab pools were analyzed, of which 22 tested SARS-CoV-2 positive (1.3%). A total of N = 315 participants took part in the survey. Across all groups, the saliva swab pool testing method was perceived as more child-friendly (>87%), convenient (>82%), and easier (>81%) compared to rapid antigen testing by an anterior nasal swab. Over 80% of all participants favored widespread, regular use of the saliva swab method. Conclusion In school settings in particular, a high acceptability of the test method is crucial for a successful SARS-CoV-2 surveillance strategy. All respondents clearly preferred the saliva swab method, which can be used safely without complications in children six years of age and older. Hurdles and suggestions for improvement of an area-wide implementation were outlined.